The Great War and Motherhood: Possibilities for Agency Within Motherhood Rhetoric 1915-1920 - (:unkn) unknown (My University, 2018)
This project seeks to understand possibilities for agency in American motherhood by looking at public motherhood discourses from 1915-1920. To accomplish this task, I use a lens of intersectionality with a mixed-methods approach of critical discourse analysis of newspaper articles and The Ladies’ Home Journal, and a textual analysis of birth control pamphlets authored by Margaret Sanger. Through these analyses, this project elucidates ways in which ideal motherhood was portrayed and prescriptively enacted through representations of nationalistic motherhood which connects principles of intensive mothering with extreme patriotism and consumerism. Ultimately, these analyses build an argument that due to the complex intersectional identities of American motherhood, birth control advocates like Margaret Sanger needed to use strategic ambiguity to discuss birth control as a tool for agency, but that agency is constrained in ways that are inseparable from race and class.
Keywords: Agency; Birth Control; Eugenics; Intersectionality; Motherhood